Manual of psychiatric nursing skills - Patel, Sudha C. (Jones & Bartlett Learning, 2012)
Manual of Psychiatric Nursing Skills guides nursing students and practicing nurses towards enhancing fundamental psychiatric nursing skills competency in specific assessment and interventions for the selected psychiatric disorders. A nursing skill book in a manual format, this text is handy at the clinical site and encourages readers to translate their theoretical knowledge and psychiatric nursing skills into clinical practice. Topics include therapeutic communication techniques, assessment and interventions for depression, bipolar disorder, schizophrenia, and suicide attempts, and crisis management skills for psychiatric emergencies. Included in the appendices are essential insights into ego defense mechanisms, Erickson s Psychosocial Developmental Stages, Freud s Stages of Psychosexual Development, and Piaget s Stages of Cognitive Development.